Encyclopedia of Careers and Vocational Guidance (Vol. 2) (New York Ferguson Publishing, 2005)
The five-volume Encyclopedia of Careers and Vocational Guidance, Thirteenth Edition is an essential resource for public, college, high school, and junior high school libraries; career centers; guidance offices; and other agencies involved with career exploration. More than 700 articles have been revised and updated since the last edition to reflect accurate, up-to-date career information. Along with revisions and updates to all articles, included here are more than 60 new career articles and more than 100 new photographs. Each article offers expanded career information, a bibliography, sidebars, and other user-friendly features. Receiving prominent treatment in this edition are the top 10 fastest-growing careers and the top 10 careers that experts predict will add the greatest number of positions through the year 2012.
Include Illustrations and Index.
Contain Career Articles, A-C.
Keywords: Occupations -- Vocational guidance